2011
DOI: 10.1253/circj.cj-11-0098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment With Pioglitazone on Reperfusion Injury in Diabetic Patients With Acute Myocardial Infarction

Abstract: Pretreatment with PIO in diabetic patients with AMI resulted in better myocardial perfusion with less reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-inducible nuclear receptor belonging to the nuclear transcription factor superfamily, 5 is a representative example. Accumulating studies demonstrate that PPARγ can protect cardiomyocytes against I/R injury through regulating cardiac oxidative stress, 6 8 inflammatory responses, 9 11 glucose and lipid metabolism, 12 14 and apoptosis. 15 17 With respect to the underlying mechanisms, PPARγ plays an essential role in regulating gene expression (eg, glucose transporter-4 [GLUT-4], 12,13 adiponectin, 18 and nuclear factor κ B inhibitor α [IκBα] 19 ), influencing transcription factors (eg, nuclear factor κ B [NF-κB] 20 ), and modulating kinase signaling pathways (eg, protein kinase B [AKT], 12,21 c-Jun N-terminal kinase [JNK], 15 and extracellular signal-regulated kinase [ERK] 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-inducible nuclear receptor belonging to the nuclear transcription factor superfamily, 5 is a representative example. Accumulating studies demonstrate that PPARγ can protect cardiomyocytes against I/R injury through regulating cardiac oxidative stress, 6 8 inflammatory responses, 9 11 glucose and lipid metabolism, 12 14 and apoptosis. 15 17 With respect to the underlying mechanisms, PPARγ plays an essential role in regulating gene expression (eg, glucose transporter-4 [GLUT-4], 12,13 adiponectin, 18 and nuclear factor κ B inhibitor α [IκBα] 19 ), influencing transcription factors (eg, nuclear factor κ B [NF-κB] 20 ), and modulating kinase signaling pathways (eg, protein kinase B [AKT], 12,21 c-Jun N-terminal kinase [JNK], 15 and extracellular signal-regulated kinase [ERK] 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…22,23) A preclinical study indicated that pioglitazone potentially ameliorates myocardial reperfusion injury, 24) but the clinical implications remain controversial. 25) Further studies are needed to determine whether reducing glucose fluctuations can provide positive results for STEMI patients undergoing reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 53 patients who had undergone the non-beating cardiac operation because of prosthetic mitral valve replacement (MVR): 26 patients with STEIRI (17 females, 9 females; mean age: 56.7±10.5 years, range: 46-67 years) and 27 patients without STEIRI (16 females, 11 males; mean age: 55.4±10.7 years, range: 45-66 years). The diagnosis of STEIRI was based on STEIRI lasting ≥30 minutes, ST-segment elevation ≥2 mm (0.2mV) in at least two contiguous electrocardiography leads (6, 7). The control group consisted of 30 normal participants (17 females, 13 males; mean age: 52.8 ±9.7 years, range: 43-62 years).…”
Section: Methodsmentioning
confidence: 99%